Extension of a protein docking algorithm to membranes and applications to amyloid precursor protein dimerization. Issue 12 (14th October 2015) - Viswanath, Shruthi; Dominguez, Laura; Foster, Leigh S.; Straub, John E.; Elber, Ron
ABSTRACT: Novel adjustments are introduced to the docking algorithm, DOCK/PIERR, for the purpose of predicting structures of transmembrane protein complexes. Incorporating knowledge about the membrane environment is shown to significantly improve docking accuracy. The extended version of DOCK/PIERR is shown to perform comparably to other leading docking packages. This membrane version of DOCK/PIERR is applied to the prediction of coiled‐coil homodimer structures of the transmembrane region of the C‐terminal peptide of amyloid precursor protein (C99). Results from MD simulation of the C99 homodimer in POPC bilayer and docking are compared. Docking results are found to capture key aspects of the homodimer ensemble, including the existence of three topologically distinct conformers. Furthermore, the extended version of DOCK/PIERR is successful in capturing the effects of solvation in membrane and micelle. Specifically, DOCK/PIERR reproduces essential differences in the homodimer ensembles simulated in POPC bilayer and DPC micelle, where configurational entropy and surface curvature effects bias the handedness and topology of the homodimer ensemble. Proteins 2015; 83:2170–2185. © 2015 Wiley Periodicals, Inc.